2020
DOI: 10.3390/cells9061347
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functions of Fubp1 in Cell Cycle Progression and Cell Survival

Abstract: The discovery of novel and critical genes implicated in malignant development is a topic of high interest in cancer research. Intriguingly, a group of genes named “double-agent” genes were reported to have both oncogenic and tumor-suppressive functions. To date, less than 100 “double-agent” genes have been documented. Fubp1 is a master transcriptional regulator of a subset of genes by interacting with a far upstream element (FUSE). Mounting evidence has collectively demonstrated both the oncogenic and tumor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…For example, FUBP1 is involved in cell survival and cell cycle progression. 7 RARS-MAD1L1 fusion gene might serve as an attractive target for therapeutic intervention for nasopharyngeal carcinoma (NPC) through the FUBP1-c-Myc axis. 8 FUBP1 serves as a cancer operator and widespread regulator of tumor suppressor, and FUBP1 participates in regulating mechanistically N6-methyladenosine (m6A) RNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FUBP1 is involved in cell survival and cell cycle progression. 7 RARS-MAD1L1 fusion gene might serve as an attractive target for therapeutic intervention for nasopharyngeal carcinoma (NPC) through the FUBP1-c-Myc axis. 8 FUBP1 serves as a cancer operator and widespread regulator of tumor suppressor, and FUBP1 participates in regulating mechanistically N6-methyladenosine (m6A) RNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…FUBP1 has been reported to be a DNA- and RNA-binding protein involved in the processes of transcription, translation, and alternative splicing ( Debaize et al, 2018 ; Debaize and Troadec, 2019 ; Elman et al, 2019 ; Kang et al, 2020 ). The phylogenetic tree analysis conducted in our study demonstrated the highly conserved nature of this protein across different species, suggesting the shared expression of FUBP1 among common ancestors of humans and animals and indicating that there may be a similar mechanism in various physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…FUBP1 encodes a multifunctional DNA and RNA‐binding protein involved in cell cycle regulation and self‐renewal of hematopoietic stem cells (HSCs) 47 . FUBP1 acts both as oncogene and as tumor suppressor, and its activity is tissue‐dependent 48 . In various tumor types FUBP1 promotes the overexpression of the MYC oncogene, 48 whereas FUBP1 silencing does not influence the expression of MYC in normal fibroblasts, prostate and bladder cancer cells 48 .…”
Section: Discussionmentioning
confidence: 99%
“…FUBP1 acts both as oncogene and as tumor suppressor, and its activity is tissue‐dependent 48 . In various tumor types FUBP1 promotes the overexpression of the MYC oncogene, 48 whereas FUBP1 silencing does not influence the expression of MYC in normal fibroblasts, prostate and bladder cancer cells 48 . Moreover, FUBP1 is involved in the upregulation and downregulation of the cell cycle inhibitor p21 49,50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation